PENGEMBANGAN BAHAN AJAR BIPA BERBASIS KONTEKS BUDAYA LOKAL UNTUK PELAJAR TINGKAT PEMULA - Huraiyah Jiratullah; Safinatul Hasanah Harahap (STKIP Subang, 2026)
This study aims to analyze the effectiveness of integrating the communicative approach and cultural elements into the Indonesian Language for Foreign Speakers (BIPA) program. Using a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and a documentary study of the learning process. The results indicate a significant improvement in international learners’ speaking and listening competencies after cultural content was systematically integrated. The use of digital technology in delivering content was found to enhance learning motivation and facilitate the acquisition of contextual vocabulary. Additionally, understanding local sociolinguistic aspects helps students communicate more politely in accordance with Indonesian social norms. The primary challenge—grammatical barriers—can be addressed through adaptive and inclusive instructor guidance in the classroom. Overall, the synergy between linguistic, cultural, and technological aspects is the key to the success of Indonesian language internationalization. These findings recommend the development of more innovative teaching materials to strengthen the position of the BIPA program on the global stage as an effective tool for cultural diplomacy.